Análise comparativa da vasculatura da íris com angiografia por tomografia de coerência óptica e contrastada com Fluoresceína - Lobos, Claudio Mauricio Zett [UNIFESP] (2019)
Introduction: The angiographic study of the iris is important to stablish a diagnosis, define medical management, monitor and/or plan surgeries of different pathological conditions of the anterior segment of the eye. The intravenous fluorescein angiography (IVFA) is the standard method for evaluation of the iris vasculature. The current technological developments give an alternative to study the iris vasculature without intravenous contrast, named optical coherence tomography angiography (OCTA). Objective: To study and compare the capability to demonstrate the iris vascular network obtained through the techniques OCT-A and IVFA in individual with and without vascular alterations of the anterior segment of the eye. Methods: Prospective, observational and transversal clinical study. All eyes were submitted to optical coherence tomography angiography (~840nm spectral domain, Avanti, Optovue Inc) using a corneal lens adapter, fluorescein angiography with confocal scanning laser ophthalmoscope (Spectralis HRA Heidelberg Engineering) or fundus camera (TRC50DX, Topcon; Visucam 500, Carl Zeiss Meditec) and digital photography of the anterior segment (DC-3, DL-D4 model, Topcon). Images of OCTA with 6 mm x 6mm scans and IVFA with focus on the iris and pupil centration, were obtained from each patient. The collected images were evaluated descriptively and quantitatively, using statistical tools and a questionnaire, based on the answer of five examiners. The concordance among the examiners regarding iris pigmentation and the percentage of visualization of the iris vasculature was evaluated using Fleiss’s coefficient of concordance, separately for each imaging technique. Differences in the capability of visualization of the vessels between the techniques were evaluated through Wilcoxon’s test. The influence of the pigmentation in the visualization of iris vasculature was evaluated using a nonparametric correlation analysis.Results: The sample included the study of 77 eyes of 39 patients (21 male and 18 female), with and without vascular alterations of the iris. The interexaminer agreement regarding the classification of iris pigmentation was moderate (k = 0,52, IC of 95%: 0,48 to 0,56, p <0,001). The interexaminer agreement regarding the evaluation of the level of the iris vasculature visualization in the images obtained by IVFA (k = 0,35, IC del 95% between 0,31 and 0,39, p <0,001) and OCTA (k = 0, 29, IC del 95% entre 0.25 y 0.34, p <0.001) was classified as regular for both techniques. Significant differences among techniques were found concerning the capability of visualizing the vessels, the images obtained by OCTA showed greater visualization capability compared to the images obtained by IVFA (W = 10.70, p <0.001). The level of pigmentation was negatively correlated with percentage of visualization of the iris vessels for the images obtained by IVFA (rho = -0.58, p <0.001), and by OCTA (rho = -0.52, p <0.001), suggesting that the more intense the pigmentation, the lesser the visualization of the vessels, regardless of the technique. Conclusions: OCTA was considered a noninvasive tool capable of visualizing the normal vessels of the iris and of detecting vascular anomalies, such as alterations of the integrity, shape and density of the iris vasculature. Early diagnosis and the study of the evolution of iris alterations become potentialities of the OCTA technique.